Performance of Black Rice with Different Nitrogen Management Practice under Mid Hill of Meghalaya - Sharma, Phurailatpam Menaka; Ray, Lala I.P. (Indian Journal of Hill Farming, 2018)
The performance of Black rice (Oryza sativa L.) was assessed under four different nitrogen sources and three planting geometry under mid hills of Meghalaya during kharif season of 2016-17. An agronomical trial was laid out with four different sources of nitrogen fertilization viz. 100% Inorganic (F1), 100% Organic (F2), 50% Organic +50% Inorganic (F3) and Control (F0) and replicated thrice. Organic source of nitrogen was Farm yard manure (FYM) and inorganic source were urea and di-ammonium phosphate (DAP). Various growth parameters like plant height (cm), number of tillers per hill, leaf area index (LAI); yield parameters like number of panicles per hill, test weight, grain yield (t ha-1); quality attributes like percentage protein, iron and zinc content in grains; and Benefit Cost Ratio (BCR) were taken into account. Plants under 50% organic + 50% inorganic source performed best among all the treatments in terms of growth, yield and quality parameters. Benefit cost ratio (BCR) was maximum with 2.12 (F3) and superior over F0, F1 and F2. The highest recorded grain yield was 1.29 t ha-1 for F3 over other three nitrogen sources.